2020
DOI: 10.1007/s00268-020-05619-7
|View full text |Cite
|
Sign up to set email alerts
|

Transition in Frailty State Among Elderly Patients After Vascular Surgery

Abstract: Background Frailty in the vascular surgical ward is common and predicts poor surgical outcomes. The aim of this study was to analyze transitions in frailty state in elderly patients after vascular surgery and to evaluate influence of patient characteristics on this transition. Methods Between 2014 and 2018, 310 patients, ≥65 years and scheduled for elective vascular surgery, were included in this cohort study. Transition in frailty state between preoperative and follow-up measurement was determined using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…And finally, 7 out of 8 studies used retrospectively collected data to determine the frailty status. Since frailty is a dynamic condition that fluctuates in time, it is difficult, if not impossible, to reliably interpret retrospectively collected results (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…And finally, 7 out of 8 studies used retrospectively collected data to determine the frailty status. Since frailty is a dynamic condition that fluctuates in time, it is difficult, if not impossible, to reliably interpret retrospectively collected results (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have measured frailty in patients undergoing vascular surgery. 35 And studies have shown that the debilitating evaluation of patients with surgery and cancer is beneficial to explore the quality of life, survival rate and recovery effect of patients. 52 Our results show that frailty is negatively correlated with compliance, this indicates that the health status of the patients after surgery needs our attention.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with chronic inflammation from limb ischaemia, tissue loss and chronic infection (often present in CLTI), it is unsurprising that a higher proportion of those with more severe CLTI are living with frailty [ 8 ]. There is some evidence that, in a small proportion of patients, frailty trajectory may be slowed or reversed after successful revascularisation in those with CLTI and frailty [ 31 ].…”
Section: Pad In Older Peoplementioning
confidence: 99%